Phase transition in dioctadecyldimethylammonium bromide and chloride vesicles prepared by different methods - Feitosa, E.; Barreleiro, PCA; Olofsson, G. (Elsevier B.V., 2000)
The gel to liquid crystalline phase transition of the double-chained cationic dioctadecyldimethylammonium chloride and bromide (DODAX, X = Cl- or Br-) in aqueous vesicle dispersions prepared by non-sonication, sonication and extrusion has been investigated using high-sensitivity differential scanning calorimetry (DSC). The transition temperature (T-m) is a function of the preparation method, amphiphile concentration, vesicle curvature and nature of the counterion. DSC thermograms for DODAB and DODAC non-sonicated vesicle dispersions exhibit a single endothermic peak at T-m roughly independent of concentration up to 10 mM. Extrusion broadens the transition peak and shifts T-m downwards. Sonication, however, broadens slightly the transition peak and tends to shift T-m upwards suggesting that extrusion and sonication form vesicles with different characteristics. DODAC always exhibits higher T-m than DODAB irrespective of the preparation method. T-m changes as follows: T-m (sonicated) greater than or equal to T-m (non-sonicated) > T-m (extruded). Hysteresis of about 7 degrees C was observed for DODAB vesicle dispersions. (C) 2000 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: differential scanning calorimetry; transition temperature; sonicated vesicles; non-sonicated vesicles; extruded vesicles